Communication strategies used by private course students - Shofie Azizah; Adip Arifin; Syamsuddin Ro’is (Concept : Community Concern for English Pedagogy and Teaching, 2025)
This study aims to investigate the types of communication strategies used by students at Ella Private Course to overcome vocabulary limitations in English-speaking activities. This study applies the communication strategy theory proposed by Faerch & Kasper (1983) and Dörnyei (1995), focusing on achievement and reduction strategies. A case study design with a qualitative approach was used, with data collected through non-participant observation and interviews. The results show that students employed a variety of strategies, including paraphrasing, approximation, non-verbal communication, code-switching, appeal for help, and stalling as achievement strategies, as well as message abandonment and topic avoidance as reduction strategies. Among these, non-verbal communication was the most dominant strategy used. These strategies helped students maintain communication despite vocabulary gaps and reflect their adaptive efforts to stay engaged in conversation. This study highlights the importance of strategic competence in supporting students’ fluency and confidence in private English learning contexts. The study strongly emphasized that recognizing the strategies students naturally use is essential to managing vocabulary limitations in real communication contexts. Besides, the findings could assist teachers and curriculum developers design to provide more effective speaking activities to strengthen learners’ communicative competence and vocabulary mastery.   Keywords: Communication strategies; challenges; vocabulary limitation